2002
DOI: 10.1002/art.10141
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of rheumatoid arthritis with anakinra, a recombinant human interleukin‐1 receptor antagonist, in combination with methotrexate: Results of a twenty‐four–week, multicenter, randomized, double‐blind, placebo‐controlled trial

Abstract: Objective. To evaluate the efficacy and safety of anakinra in combination with methotrexate (MTX) in patients with active rheumatoid arthritis (RA).Methods. Patients with moderate-to-severe active RA who were receiving MTX for 6 consecutive months, with stable doses for >3 months (those with disease duration of >6 months but <12 years) were randomized into 6 groups: placebo or 0.04, 0.1, 0.4, 1.0, or 2.0 mg/kg of anakinra administered in a single, daily, subcutaneous injection. The primary efficacy end point w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
316
2
16

Year Published

2003
2003
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 573 publications
(347 citation statements)
references
References 40 publications
11
316
2
16
Order By: Relevance
“…Other than ISRs, the most common adverse event was worsening of symptoms of RA, occurring in 223 anakinra patients (20% of those reporting adverse events) and 78 placebo patients (27.6% of those reporting adverse events). These adverse event rates are consistent with those observed in previous clinical studies of anakinra in patients with RA (24,25). In the anakinra group, the rate of ISRs was higher among Serious adverse events occurred at a similar frequency in the 2 treatment groups, with 86 patients in the anakinra group (7.7%) and 22 patients in the placebo group (7.8%) experiencing serious events.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…Other than ISRs, the most common adverse event was worsening of symptoms of RA, occurring in 223 anakinra patients (20% of those reporting adverse events) and 78 placebo patients (27.6% of those reporting adverse events). These adverse event rates are consistent with those observed in previous clinical studies of anakinra in patients with RA (24,25). In the anakinra group, the rate of ISRs was higher among Serious adverse events occurred at a similar frequency in the 2 treatment groups, with 86 patients in the anakinra group (7.7%) and 22 patients in the placebo group (7.8%) experiencing serious events.…”
Section: Resultssupporting
confidence: 90%
“…The other notable difference between treatments was the occurrence of ISRs. There were significantly more ISRs in the anakinra group (72.6%) than in the placebo group (32.9%), an observation that is consistent with previous studies of anakinra (24,25) and other injected biologic agents (29)(30)(31)(32)(33) in the treatment of patients with RA. As in those studies, the ISRs observed in the present study were typically mild to moderate.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations